Costs and cost-effectiveness of robotic-assisted surgery in South Korea: a systematic review and meta-analysis - Hong, Young Eun; Shim, Hana; Shin, Minkyung (Frontiers in Public Health, 2025)
IntroductionRobot-assisted surgery (RAS) has rapidly expanded across multiple surgical specialties since being introduced in South Korea. RAS has been proven clinically safe and effective, but its economic implications have not been thoroughly investigated. As public reimbursement for RAS is increasingly adopted by Asian countries such as Japan and Taiwan, the economic implications of RAS have become a critical factor in influencing reimbursement decisions in Korea.MethodWe conducted a systematic review and meta-analysis of studies reporting cost and cost-effectiveness of RAS in Korea, published between 2007 and March 2025. Studies were searched using three databases: PubMed, EMBASE, and Scopus. Two authors independently performed literature screening, data extraction and risk of bias assessment using ROBINS-I and RoB. Outcomes were analyzed through meta-analysis with RevMan.ResultsA total of 24 were included, comprising two randomized controlled trials (RCT) and 22 observational studies. Most studies were conducted at single institutions. Colorectal surgery was the most frequently studied procedure. For RAS, total hospitalization costs ranged between $6,762 and $20,206, while laparoscopic or endoscopic surgery spanned from $3,038 to $11,933, and open surgery costs ranged from $1,706 to $9,009. The meta-analysis demonstrated that the mean difference in total hospitalization cost between RAS and laparoscopic surgery was $3,279 (95% CI: $2,414 to $4,145; I2:95%).ConclusionThis is the first comprehensive systematic review and meta-analysis specifically assessing the economic implications of RAS in Korea. Our findings indicate that RAS is more costly than other surgical modalities at the time of surgery. However, the current review identified a lack of evidence on post-discharge costs, and no comprehensive cost-effectiveness or cost-utility analyses have been conducted in Korea. Future studies are encouraging to explore the long-term costs across different modalities.